Maturation of the equine medial femoral condyle osteochondral unit. Issue 1 (March 2020) - Lemirre, T.; Santschi, E.; Girard, C.; Fogarty, U.; Chapuis, L.; Richard, H.; Beauchamp, G.; Laverty, S.
Summary: Objective: The juvenile equine medial femoral condyle (MFC) is frequently affected with radiographic changes (sclerosis and subchondral lucencies) that arise at a similar site to juvenile osteochondritis dissecans (JOCD) in children. There is little information on maturation of the MFC. To describe the normal development of the equine MFC osteochondral unit from birth to 2 years. Methods: Micro CT, histology and immunohistochemistry were performed on healthy equine MFCs (n = 29) at sites where lesions occur. Parameters assessed included: cartilage thickness; the epiphyseal growth plate cartilage organization; the osteochondral junction and progression of endochondral ossification. Results: From 0 to 6 months, chondrocytes near the articular surface are small and flat and have a characteristic hypertrophic appearance near the osteochondral junction but are not arranged in columns like physeal growth plates. The osteochondral junction is also crossed by cartilage canals containing vessels giving a porous appearance on 3D μCT images. At 7 months of age, a subchondral bone plate compact structure emerged histologically coincident with the end of endochondral ossification (absence of type X collagen immunostain and chondrocyte hypertrophy). Conclusion: New information is provided on MFC osteochondral unit maturation that will improve our understanding of the development of juvenile equine orthopaedic disease. Equine MFC endochondral ossification is complete at 6 months of age. The immature osteochondral junction may be structurally fragile because of its microarchitecture and susceptible to focal traumatic events that induce developmental lesions.